Factors affecting Consumer Purchase Intention of Luxury Perfumes in Algeria: A case study of Consumers in the Twin Cities of Tlemcen and Sidi Bel Abbes - Chihab, Zaidi Oussama; Abderrezzak, Benhabib (Journal of Research in Marketing (ISSN: 2292-9355), 2016)
In Algeria, few studies on the factors behind purchase intention of luxury perfumes have been undertaken; the main objective of this research is to study the influence of brand image, social and functional values as well as past behaviour on the purchase intention of luxury perfumes in Algeria, using the theory of reasoned action. This study also aims at demonstrating the impact of social and functional values on attitude. Based on the literature review, a conceptual model is proposed. An empirical study is then conducted among a sample of 306 persons in the twin cities of Tlemcen and Sidi Bel Abbes. Results drawn with the use of the partial least squares applied to structural equation modeling method, show that social and functional values have a significant positive effect on attitude. The results also show, on one hand, that each of the price-quality, brand image, past behaviour and attitude variables have a significant positive impact on purchase intention of luxury perfumes; and, on the other hand, they do not show any significant effect of subjective norm, need for uniqueness and social value on purchase intention of luxury perfumes.